2010
DOI: 10.1007/s10995-010-0627-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approaches to Improve Birth Outcomes: Perinatal Periods of Risk, Infant Mortality Review, and the Los Angeles Mommy and Baby Project

Abstract: This article provides an example of how Perinatal Periods of Risk (PPOR) can provide a framework and offer analytic methods that move communities to productive action to address infant mortality. Between 1999 and 2002, the infant mortality rate in the Antelope Valley region of Los Angeles County increased from 5.0 to 10.6 per 1,000 live births. Of particular concern, infant mortality among African Americans in the Antelope Valley rose from 11.0 per 1,000 live births (7 cases) in 1999 to 32.7 per 1,000 live bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…A long history of research has consistently shown a positive association between an individual's perception of the availability of social support and health outcomes (Aneshensel & Stone, 1982;Berkman, 1984;Burleson & MacGeorge, 2002;Cohen, 1988;House et al, 1988;Krause, 1990). The positive benefits of social support have been seen across a range of health issues, such as cancer (Epplein et al, 2011;Uchino, 2004); cardiovascular disease (Uchino, 2006); diabetes (Griffith, Field, & Lustman, 1990); and pregnancy (Blake, Kiely, Card, ElMohandes, & El-Khorazaty, 2007;Chao et al, 2010;Chomitz, Cheung, & Lieberman, 1995;Conway & Kennedy, 2004;Cronenwett, 1985;Dejin-Karlsson, et al, 2000;Feldman, Dunkel-Schetter, Sandman, & Wadhwa, 2000;Liese, Snowden, & Ford, 1989;Sable & Wilkinson, 2000).…”
Section: Social Support and Healthmentioning
confidence: 99%
“…A long history of research has consistently shown a positive association between an individual's perception of the availability of social support and health outcomes (Aneshensel & Stone, 1982;Berkman, 1984;Burleson & MacGeorge, 2002;Cohen, 1988;House et al, 1988;Krause, 1990). The positive benefits of social support have been seen across a range of health issues, such as cancer (Epplein et al, 2011;Uchino, 2004); cardiovascular disease (Uchino, 2006); diabetes (Griffith, Field, & Lustman, 1990); and pregnancy (Blake, Kiely, Card, ElMohandes, & El-Khorazaty, 2007;Chao et al, 2010;Chomitz, Cheung, & Lieberman, 1995;Conway & Kennedy, 2004;Cronenwett, 1985;Dejin-Karlsson, et al, 2000;Feldman, Dunkel-Schetter, Sandman, & Wadhwa, 2000;Liese, Snowden, & Ford, 1989;Sable & Wilkinson, 2000).…”
Section: Social Support and Healthmentioning
confidence: 99%
“…Importantly, residential mobility during pregnancy was shown to be related to risk factors of adverse pregnancy outcomes, including age, smoking, and socioeconomic status (Miller et al, 2010), all of which may act as confounders (Bell and Belanger, 2012). Other potential confounders in studies of reproductive outcomes include place of birth, medical and obstetric history (e.g., infections and medication use), lifestyle characteristics other than smoking (e.g., nutrition and alcohol use), as well as numerous pregnancy-related factors, such as initiation of prenatal care, weight gain during gestation, and prenatal complications (Shi and Chia, 2001;Chao et al, 2010). Among studies included in the current review, there appeared to be no consistency in terms of control for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the action statements can be used to further the work of the Perinatal Periods of Risk (PPOR) approach [53][54][55][56]. PPOR, a comprehensive approach to help communities use data to reduce infant mortality, was designed for use in urban areas with high infant mortality rates.…”
Section: Discussionmentioning
confidence: 99%